2021
DOI: 10.1002/hep.31673
|View full text |Cite
|
Sign up to set email alerts
|

H19 Promotes HCC Bone Metastasis Through Reducing Osteoprotegerin Expression in a Protein Phosphatase 1 Catalytic Subunit Alpha/p38 Mitogen‐Activated Protein Kinase–Dependent Manner and Sponging microRNA 200b‐3p

Abstract: Background and Aims Bone is the second most frequent site of metastasis for HCC, which leads to an extremely poor prognosis. HCC bone metastasis is typically osteolytic, involving the activation of osteoclasts. Long noncoding RNA H19 plays an important role in the pathogenesis of human cancers. Nonetheless, the mechanism underlying the participation of H19 in HCC bone metastasis remains unclear. Approach and Results The current study established a mouse HCC bone metastasis model by using serial intracardiac in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…2 A). While the expression levels of PA2G4 in HCC cells with the same genetic background were in accordance with metastatic ability [ 41 ], which further implied its involvement in HCC metastasis process (Fig. 2 B).…”
Section: Resultsmentioning
confidence: 82%
“…2 A). While the expression levels of PA2G4 in HCC cells with the same genetic background were in accordance with metastatic ability [ 41 ], which further implied its involvement in HCC metastasis process (Fig. 2 B).…”
Section: Resultsmentioning
confidence: 82%
“…Studies have shown that in highly aggressive liver cancer cells, the expression of TNFRSF11B is often lower than that of low aggressive liver cancer cells [ 58 ]. The same point of view is that the down-regulation of TNFRSF11B expression can promote HCC bone metastasis in vivo [ 59 ]. However, there is also evidence that the high expression of TNFRSF11B is an important reason for the high metastatic potential of HCC cells [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, H19 is a cytoplasmic lncRNA that can sponge miRNAs to modulate gene expression [26]. Several miRNAs have been shown to directly interact with H19, including miR-141-3p, miR-200b-3p, and let-7a [34][35][36]. It is therefore likely that the effects of H19 on normal and cancer cells are determined by the complex interplay of a pool of cell-specific miRNAs expressed in each cell type.…”
Section: Discussionmentioning
confidence: 99%